1997
DOI: 10.1183/09031936.97.10091946
|View full text |Cite
|
Sign up to set email alerts
|

Eotaxin protein and gene expression in guinea-pig lungs: constitutive expression and upregulation after allergen challenge

Abstract: Eotaxin is an eosinophil-specific chemoattractant originally identified in bronchoalveolar lavage fluid after allergen challenge of sensitized guineapigs. We have determined and quantified for the first time the cellular sources of guinea-pig lung eotaxin and localized gene expression in structural cells of large and small airways and in alveolar macrophages.We used anti-guinea-pig eotaxin monoclonal and polyclonal antibodies and a complementary ribonucleic acid (cRNA) probe to detect eotaxin protein and cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
19
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 41 publications
4
19
0
Order By: Relevance
“…Further, a concomitant expression of CXCL10 in ASM cells and CXCR3 (CXCL10 receptor) in mast cells was also observed within ASM of subjects with asthma [20]. Studies in animal models of allergen-induced airway hyperresponsiveness detected eotaxin, an eosinophilspecific chemoattractant mediator, in bronchial ASM of guinea pigs [21].…”
Section: Chemokinesmentioning
confidence: 96%
“…Further, a concomitant expression of CXCL10 in ASM cells and CXCR3 (CXCL10 receptor) in mast cells was also observed within ASM of subjects with asthma [20]. Studies in animal models of allergen-induced airway hyperresponsiveness detected eotaxin, an eosinophilspecific chemoattractant mediator, in bronchial ASM of guinea pigs [21].…”
Section: Chemokinesmentioning
confidence: 96%
“…Upon activation, cultured human ASM (HASM) cells secrete large amounts of eotaxin, regulated on activation, normal T expressed and secreted (RANTES), IL-6, vascular endothelial growth factor (VEGF), IL-8, monocyte chemoattractant protein-1 (MCP-1), MCP-2, and MCP-3 (4-7). In vivo, the expression of eotaxin is increased in guinea-pig ASM after allergen challenge (8), and both eotaxin and RANTES are highly expressed in the smooth muscle layer of the airways in patients with asthma (3,4,9). A recent study also showed that the mediators produced by human ASM promoted the differentiation of eosinophils from blood progenitor cells (10).…”
mentioning
confidence: 87%
“…Glucocorticoids potently inhibit airway eosinophilia by actions at all stages of the abovementioned processes. 1,[7][8][9] Eosinophilic inflammation is regulated to a major extent by activated T lymphocytes in the airways that secrete the T H 2 cytokine IL-5. This cytokine is a central mediator in the regulation of eosinophilic inflammation through effects on the proliferation, differentiation, and activation of eosinophils, 10,11 as well as providing a signal for the rapid mobilization of eosinophils from the bone marrow.…”
mentioning
confidence: 99%